2022
DOI: 10.1186/s40249-022-01010-x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the spatial distribution of environmental and socio-economic suitability for human leptospirosis in the face of limited epidemiological data

Abstract: Background Leptospirosis is among the leading zoonotic causes of morbidity and mortality worldwide. Knowledge about spatial patterns of diseases and their underlying processes have the potential to guide intervention efforts. However, leptospirosis is often an underreported and misdiagnosed disease and consequently, spatial patterns of the disease remain unclear. In the absence of accurate epidemiological data in the urban agglomeration of Santa Fe, we used a knowledge-based index and cluster a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…First, spatially aggregated data mask the effects of hydrometeorological drivers of disease at finer spatial scales. A recent analysis of the spatial distribution of leptospirosis suitability in Santa Fe province has shown that there is marked difference with elevation, urban and suburban structure, and environmental conditions [ 30 ]. Most leptospirosis cases were reported in the largest cities and in some of them there are other water bodies, such as the Salado River in Santa Fe.…”
Section: Discussionmentioning
confidence: 99%
“…First, spatially aggregated data mask the effects of hydrometeorological drivers of disease at finer spatial scales. A recent analysis of the spatial distribution of leptospirosis suitability in Santa Fe province has shown that there is marked difference with elevation, urban and suburban structure, and environmental conditions [ 30 ]. Most leptospirosis cases were reported in the largest cities and in some of them there are other water bodies, such as the Salado River in Santa Fe.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution pattern analysis functions to determine spatial variations, both in the incidence of a disease and its risk factors. With spatial analysis, a mapping process can be Vol 6 carried out to determine the geographic distribution of potential disease risks and their relationship with existing environmental risk factors (Cristaldi et al, 2022). Based on malaria elimination data, in 2014 in North Sumatra province 15 out of 33 districts/cities had received malaria elimination certificates.…”
Section: Introductionmentioning
confidence: 99%